2011
DOI: 10.1039/c0nr00767f
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced hydrogen storage by spillover on metal-doped carbon foam: an experimental and computational study

Abstract: A lightweight, oxygen-rich carbon foam was prepared and doped with Pd/Hg alloy nanoparticles. The composite revealed high H2 sorption capacity (5 wt%) at room temperature and moderate pressure (2 MPa). The results were explained on the basis of the H2 spillover mechanism using Density Functional Theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 16 publications
0
39
0
6
Order By: Relevance
“…A detailed pore size distribution (PSD) analysis was carried out by applying the Quenched Solid Density Functional Theory (QSDFT) kernel for slit/cylinder-like shape pores in the recorded N 2 desorption data [35]. 8 3 Results and discussion The aforementioned morphology was also investigated in more detail using high-resolution TEM analysis ( Fig. 2g and 2h).…”
Section: Characterization Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed pore size distribution (PSD) analysis was carried out by applying the Quenched Solid Density Functional Theory (QSDFT) kernel for slit/cylinder-like shape pores in the recorded N 2 desorption data [35]. 8 3 Results and discussion The aforementioned morphology was also investigated in more detail using high-resolution TEM analysis ( Fig. 2g and 2h).…”
Section: Characterization Methodsmentioning
confidence: 99%
“…and other compounds, such as metallic-and/or inorganic-based nano-sized particles, clusters or thin films [1][2][3][4][5]. Such composite materials may exhibit a combination of properties favorable for rapidly expanding and materials-oriented research areas, including gas sensing [6], carbon dioxide conversion [7], hydrogen storage [8], electrochemical energy storage [9], water treatment [10] and capacitive desalination [11]. Their promising performance in such applications is attributed not only to the individual characteristics of the host carbonaceous support and the hosted/embedded substance, but also to the potential synergy between the two.…”
Section: Introductionmentioning
confidence: 99%
“…Exploring safe and efficient materials remains a great challenge. [1][2][3][4][5][6] Among many practical hydrogen storage materials, NH 3 BH 3 (AB) is believed to be a prominent candidate owing to its high hydrogen content (19.6 wt %), [7] excellent solubility, and stability in water. However, the hydrogen generation rate of AB in the absence of suitable catalysts is very slow, which seriously restricts its development as a promising hydrogen storage material.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work by Psofogiannakis et al (2011) has shown that carbon foams have a very low storage density of 0.045 wt% hydrogen at 298 K and 20 bar pressure. Since the physical properties of the foam material employed by Psofogiannakis et al (2011) were not described in detail, they might differ from the foam structure we have used for GCMC simulations. However, the observation of a low gravimetric density in foam from simulations seems to be in fair agreement with the experimental results.…”
Section: Physisorption Of Hydrogen In Nanoporous Structuresmentioning
confidence: 99%